2013
DOI: 10.1007/s12070-013-0683-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Unique ‘Inverted U’ Shaped Thyroid Gland and Its Clinical Importance

Abstract: Thyroid anomalies are not uncommon. Two lobes are usually connected by isthmus at the level of 2-4 tracheal rings. We encountered a unique variation in which thyroid lobes were connected near upper pole by an isthmus at the level above the cricoid cartilage giving an 'inverted U' shape to the thyroid gland. Such unusual variation in thyroid gland has not been reported earlier in the literature. The sound knowledge of such variation should be important to the surgeon while operating on thyroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Marshall [9] also reported a case of double pyramidal lobe. Mangalgiri et al [14] reported a case of inverted U shaped thyroid gland in which two lobes were joined by isthmus above cricoid cartilage. In complete exposure in such may be mistaken for bilateral pyramidal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Marshall [9] also reported a case of double pyramidal lobe. Mangalgiri et al [14] reported a case of inverted U shaped thyroid gland in which two lobes were joined by isthmus above cricoid cartilage. In complete exposure in such may be mistaken for bilateral pyramidal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the complications of thyroid surgeries, i.e., recurrent laryngeal nerve injuries, have reduced, and injury or unintentional removal of the parathyroid glands with resultant hypoparathyroidism is more competitive. 10 The nerve injuries have reduced below single digits even in the hands of beginners and are hardly fatal. And so the surgery of the thyroid is basically to preserve the parathyroid, and hence the emphasis is doubled in case of surgery done for pathology of thyroid hemiagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The parathyroid dysfunction may be evident in 24 to 48 hours depending on the reserves of calcium nutrition of the individual. 10 The parathyroids vary in their anatomy ranging from 1 to 12 glands in number, but most commonly, they are four (two superior and two inferior) in 87% cases while three in 6%, five in 0.2%, and six in 0.6% cases. 11 Intraoperatively, all the four glands can be visualized in total thyroidectomy in only half of the cases, while the area lodging the parathyroids would be the middle i/3 of the thyroid gland posterior surface in two-third of the cases.…”
Section: Discussionmentioning
confidence: 99%